Focus on sources of negatively charged ions. (20th June 2018) - Fantz, Ursel; Lettry, Jacques
Abstract: This focus issue presents theoretical investigations, modelling and technical achievements across the large variety of sources of negatively charged ions (NCI). The twenty contributions cover a fraction of the very broad range of applications requiring very different time structure, intensities and beam energies. The world's largest NCI source area is 1 × 2 m 2 and shall provide 1280 beamlets of ∼30 mA intensity each, while the smallest unit of our selection is only a few mm 2 and requires the highest ionization efficiencies to deliver negative radioisotope-ions far from stability produced via nuclear reactions at rates down to or below few atoms per seconds.